PENGGUNAAN PUPUK HAYATI PELARUT FOSFAT DAN PUPUK P TERHADAP PERTUMBUHAN KELAPA SAWIT ( Elaeis quineensis Jacq ) DI PEMBIBITAN UTAMA PADA TANAH ULTISOL - Ida Nursanti (Universitas Batanghari Jambi, 2010)
To get the planting medium that can support plant growth, especially on marginal land such as the type Ultisol required the addition of biological material and nutrients through fertilization. This study aims to obtain bio-fertilizer and P fertilizer phosphate solvent appropriate to the Ultisol order to support the growth of oil palm seedlings in a nursery optimal primary. The experiment was conducted in the city of Jambi using factorial completely randomized design consisting of biological treatment of solvent phosphate fertilizer (0, 30 and 60g of plant-1) and P fertilizer (0, 4.45 g and 9.80 g plant-1) and there were three replications with nine treatment combinations. The results showed that the treatment effect is very significant effect on seedling height, stem diameter, leaf area, dry weight of crowns and roots. In general it can be concluded that the solvent of biological fertilizer and phosphate fertilizer P is very influential on the growth of oil palm seedlings in the main nursery on Ultisol. Solvent biological phosphate fertilizer plant 60g-1 and P fertilizer dose of 4.45 g is the best in supporting the growth of oil palm seedlings in the main nursery. Keyword : Oil palm seeds, Ultisol, P fertilizer, biological fertilizer phosphate solvent